PERANAN PROGRAM COMMUNITY DEVELOPMENT PERUSAHAAN BATUBARA MENINGKATKAN KESEJAHTERAAN MASYARAKAT (STUDI KASUS KABUPATEN TANAH BUMBU, KALIMANTAN SELATAN) - Wulan Metafurry; Bambang Juanda; Eka Intan Kumala Putri (Diponegoro University, 2016)
Community development (comdev) is a form of corporate social responsibility program to increase community welfare. On the other side, comdev also aims to minimize the impact arising from mining activities. The present study aims to analyze the benefit of comdev and to calculate comdev contribution to increase community welfare. The method used to answer the research are Second Order Confirmatory Factor Analysis (2nd CFA) and Multiple Linier Regression with Principal Component Analysis (PCA). The result show that benefit of comdev was perceived by community in Tanah Bumbu, South Kalimantan. Comdev also contributes positively to increase human resource development in Tanah Bumbu, but comdev not enough to compensate for the negative impact of mining especially enviromental issues.